Minorities and Indigenous Peoples: A Comprehensive Review - Tomar, Umang (International Journal of Law, Human Rights and Constitutional Studies; Vol 5 No 1 (2023): International Journal of Law, Human Rights and Constitutional Studies, 2023)
This comprehensive review delves into the intricate tapestry of minorities and indigenous peoples, exploring their historical contexts, contemporary challenges, legal frameworks, and the tireless efforts towards achieving social justice and equality. The historical dimension uncovers the deep-rooted discrimination stemming from colonization, emphasizing indigenous peoples' remarkable resilience in preserving their cultural heritage. The contemporary challenges section underscores persistent disparities in land rights, education, health, and discrimination, highlighting the urgent need for change. The review examines international legal instruments and landmark court cases that underpin the protection of these communities, while addressing the formidable challenges in their implementation. Efforts towards social justice and equality come to the forefront, with grassroots movements advocating for land rights, cultural preservation, and self-determination. Collaborative initiatives involving governments, NGOs, and international organizations are explored in the context of economic development, cultural preservation, and self-governance. Education and awareness campaigns, inclusive of media and cultural festivals, play a pivotal role in challenging stereotypes and fostering understanding. In conclusion, this review underscores the enduring significance of acknowledging and supporting minorities and indigenous peoples, emphasizing the imperative of a global commitment to justice and inclusivity for all, irrespective of their cultural background or ethnicity